Willows in Patagonia: the challenge of understanding and controlling invasions - Orellana Ibáñez, Ivonne Alejandra; Amico, Ivana Lourdes; Vincón, Sergio Gabriel; Bonansea, Tomas (Universidad Autónoma del Estado de México (UAEMEX), 2022)
Exotic willows are widely spread throughout Patagonia due to their vegetative multiplication, rapid growth, and ease for establishing themselves in environments with fluctuating hydric regimes, so they most commonly overgrow in riverside environments and wetlands. We identified exotic willow species on the Futaleufú and the Chubut rivers basins, which cover roughly 65,000 km2 in the Chubut Province of Argentina. We also surveyed and determined the western distribution boundary of Salix humboldtiana – the only native willow in the Southern Hemispere. In addition, we documented occurrences of natural hybridization between S. humboldtiana and Salix x fragilis. An important objective of the survey included developing control methods for S. x fragilis to prevent regrowth. We shared such research activities with socially interested groups through extension, release, and other related activities. The involvement of scientific and technical sectors in socio-environmental issues enables the use of friendly tools geared towards the sustainable development of local domestic economies while preserving the environment’s biological diversity.